Effect of the plant density on different maize (Zea mays L.) hybrids yields and leaf area index (LAI) values - Murányi, Eszter (Acta Agraria Debreceniensis, 2015)
We have investigated the plant number reactions of three maize hybrids of various genotypes in a small-plot field experiment. The plant numbers were 50, 70 and 90 thousand ha-1, while the row distances were 45 and 76 cm. The experiment was set on the Látókép Experimental Farm of Centre for Agricultural Sciences of the University of Debrecen in four replications on calcareous chernozem soil.The assimilation area and the leaf area index have important role in development of the crop yield. The studied three different genotype maize hybrids reached its maximum leaf area index at flowering. The maximum leaf area index increased linearly with increasing plant density. The season-hybrids reached less yield and leaf area index. According to our experimental results, we have concluded that with the decrease of the row spacing, the yield increased in the average of the hybrids. The studied hybrids reached the maximum yield at 70 and 90 plants ha-1 plant density. We determined the optimal plant number that is the most favourable for the certain hybrid under the given conditions.The higher plant density was favourable at 45 cm row spacing than 76 cm. The hybrids reached the maximum grain yield at 45 cm row spacing between 76 712–84 938 plants ha-1, while the optimum plant density at 76 cm row spacing changed between 61 875–65 876 plants ha-1.The leaf area index values between the applied plant density for the flowering period (July 1, 24), we defined a significant differences. In the archived yields were significant differences at the 45 cm row spacing between 50 and 70, 90 thousand ha-1 plant density, while the number for the 76 cm row spacing used did not cause a significant differences in the yield. There were significant differences between the examined hybrids of yields.